Handbook of compound semiconductors : growth, processing, characterization, and devices - Holloway, Paul H.; McGuire, G. E. (Noyes Publications, 1995)
This book reviews the advances and technologies used to produce microelectronic and optoelectronic devices from compound semiconductors. It provides an overview of the technologies necessary to grow bulk single-crystal substrates, grow hetero-or homoepitaxial films, and process advanced devices such as HBT's, QW diode lasers, etc.
Keywords: Compound semiconductors -- Handbooks, manuals, etc.; elektronické knihy; electronic books